Quality of life and related factors of patients with Brugada syndrome type 1 at King Chulalongkorn Memorial Hospital - Sutjaporn, Boosamas; Tunvirachaisakul, Chavit; Khongphatthanayothin, Apichai (Chulalongkorn Medical Journal, 2022)
Background: Brugada syndrome (BrS) is a rare cardiac arrhythmic syndrome which can increase the risk of sudden cardiac death in patients without structural heart disease. BrS may affect patients’ quality of life due to long-term follow-up. Objective: To identify the quality of life and related factors in patients with BrS. Methods: Twenty-nine patients with BrS from King Chulalongkorn Memorial Hospital were recruited between August 2019 to April 2020. We collected demographic data, evaluated depression/anxiety with Thai-HADS test, and administered cognitive tests and the quality of life questionnaires (MacNew and SF-36). Descriptive and multiple linear regression were used to analyze the data. Results: There were 28 male and 1 female subjects. The average age was 45.2 13.8 years old. The result of MacNew questionnaire score was 5.6 0.8. For SF-36, the physical component score was 49.8 6.4 and mental component score was 52.9 6.3. The score of anxiety and depression from HADS was 4.4 2.9 and 3.3 3.3, respectively. For the cognitive test, the following results were observed; the Grooved Pegboard on dominant (78.4 27.9 seconds) and non-dominant (84.5 26.0 seconds), Trail A (53.7 20.7 seconds) and B (181.0 80.9 seconds), and memory tests (Word List Memory 21.0 4.4 words; recall 7.2 2.6 words; and recognition 9.6 1.0 words). From multiple regression analysis, only the anxiety score from HADS had a statistically significant impact on the quality of life. Conclusion: Most BrS patients had a moderate quality of life and anxiety was an essential predictor for quality of life in BrS patients.